For the Sake of Protecting Physcal Needs: Maqasid Sharia Perspective Toward Judges Consideration on Child Custody - Zuhdi Hasibuan (State Islamic University (UIN) of Sunan Ampel, 2023)
In Islamic law, for a child who has not been mumayyiz, their custody falls in the hands of the mother. If the child has been mumayyiz, then the child is given the right to choose and determine who has the right to care for him. However, the judge of Panyabungan Religious Court decides the custody of a child who has not been mumayyiz to the father. This study aims to analyze the judge’s considerations in determining the custody of a child who has not been mumayyiz to the father. Using a normative and philosophical approach by using Maqasid Sharia theory, this study employs a qualitative methodology to examine the judge’s consideration. As for the results of this study, firstly, in consideration of the judge stipulating the custody of the child who has not been mumayyiz to the father is to maintain the child’s physical growth. Second, the author believes that a judge who determines to whom child custody is granted should prioritize the existence of religion over the existence of the soul. It means that child custody is given priority to one of the parents with better religion, behavior, and association than prioritizing the child's physical needs.